Ferulic acid protects against heat stress-induced intestinal epithelial barrier dysfunction in IEC-6 cells via the PI3K/Akt-mediated Nrf2/HO-1 signaling pathway. (1st January 2019) - He, Shasha; Guo, Yuhong; Zhao, Jingxia; Xu, Xiaolong; Song, Jin; Wang, Ning; Liu, Qingquan
Abstract: Purpose: Intestinal epithelial barrier dysfunction is crucial in the pathogenesis of intestinal and systemic diseases. Ferulic acid (FA) possesses promising antioxidant activities. In a previous study, we demonstrated potentially protective effects of FA against heat stress- induced intestinal epithelial barrier dysfunction in IEC-6 cells. However, the underlying mechanisms are unclear. The present study aimed to elucidate whether FA protects IEC-6 cells from heat stress-induced intestinal epithelial barrier dysfunction via antioxidative mechanisms. Materials and methods: IEC-6 cells were pretreated with FA prior to hyperthermia exposure at 42 °C for 6 h, and the levels of intracellular reactive oxygen species (ROS), malondialdehyde (MDA), nitrogen oxide (NO), and superoxide dismutase (SOD) activity were analyzed. The intestinal epithelial barrier function was determined by transepithelial electrical resistance (TER) values and 4-kDa fluorescein isothiocyanate-dextran (FD4) flux in IEC-6 cell monolayers. Expression of related proteins was detected by Western blotting. Results: FA suppressed heat stress-induced intestinal oxidative stress damage by reducing ROS, MDA and NO production, while enhancing SOD activity. Furthermore, FA treatment strengthened intestinal barrier function via increasing the phosphorylation levels of Akt, nuclear factor-erythroid 2-related factor 2 (Nrf2) and hemeoxygenase-1 (HO-1) protein expression, which was reversed by zinc protoporphyrin (an HO-1 inhibitor). Additionally, LY294002, a specific PI3K/Akt inhibitor, significantly suppressed FA-induced Nrf2 nuclear translocation and HO-1 protein expression and inhibited FA-induced occludin and ZO-1 protein expression. Conclusions: FA protected against heat stress-induced intestinal epithelial barrier dysfunction via activating the PI3K/Akt-mediated Nrf2/HO-1 signaling pathway in IEC-6 cells.